2018
DOI: 10.3390/rs10071018
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of the Potential of Landsat 8 in Estimating Chlorophyll-a, Ammonium Concentrations and Other Water Quality Indicators

Abstract: In-situ monitoring of lake water quality in synergy with satellite remote sensing represents the latest scientific trend in many water quality monitoring programs worldwide. This study investigated the suitability of the Operational Land Imager (OLI) instrument onboard the Landsat 8 satellite platform in accurately estimating key water quality parameters such as chlorophyll-a and nutrient concentrations. As a case study the largest freshwater body of Greece (Trichonis Lake) was used. Two Landsat 8 images cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 66 publications
1
43
0
1
Order By: Relevance
“…Combining in situ and RS data for water-quality monitoring allows a holistic analysis that can provide alternative management scenarios [243]. Coastal and ocean monitoring are challenging due to multiple sources that modify physico-biological processes [244].…”
Section: Water Qualitymentioning
confidence: 99%
“…Combining in situ and RS data for water-quality monitoring allows a holistic analysis that can provide alternative management scenarios [243]. Coastal and ocean monitoring are challenging due to multiple sources that modify physico-biological processes [244].…”
Section: Water Qualitymentioning
confidence: 99%
“…Such systems also do not require accuracy of edge detection, therefore use of freely available moderate resolution remote sensing is appropriate for most purposes. Trophic status indicators include chlorophyll-a [52,308], turbidity (Secchi disk depth), total phosphorus [216], and coloured dissolved organic carbon or matter [28,221]. Sass et al [222] found that red and red/blue wavelengths from Landsat 4/5 and 7 were the most accurate indicators of trophic status, including accuracies of approximately 80% (chlorophyll-a), 90% (turbidity), and (-)70% (Secchi disk depth).…”
Section: Remote Sensing Of Wetland Biogeochemistrymentioning
confidence: 99%
“…Locations of the two study areas are shown in color composite images (R6G3B2) in Figure 3. The flooding reference images were obtained from the corresponding Landsat 8 OLI images using the modified normalized difference water index (mNDWI) [37,38]. The resolution of the flooding reference images was 30 m. The flooding fraction images were obtained by aggregating the corresponding flooding reference images.…”
Section: Study Materialsmentioning
confidence: 99%